Family planning in the Unified Health System: Use of the intrauterine device (Research, Society and Development, 2022)
Introduction: The Intrauterine Device (IUD) is a long-acting reversible contraceptive method, which causes an inflammatory reaction, developing biochemical and morphological changes, which can trigger minimal tissue damage, which make the environment sterile, altering the cervical mucus and acting as a spermicide, preventing pregnancy, so that ovulation is not affected. Objective: To analyze the insertion and removal of the IUD by the Unified Health System during the years 2020 to 2021. Methodology: Ecological study with an exploratory and quantitative approach based on data obtained from the Department of Informatics of the Unified Health System (DATASUS) on the insertion of the IUD in Brazil between August 2020 and August 2021. It is possible to analyze the growth rate of both the insertion rate and the rate of withdrawal of the same, in addition to the rates by Regions, States, Nursing professionals and professionals of Medicine. Results: In the period from August 2020 to August 2021, 53,118 notifications were registered, 87% of which were insertions and 13% were withdrawn. Highlighting the State of São Paulo located in the Southeast region with 17,279 IUD insertion notifications (37.38%). In addition to obtaining insertion data by nurses, of which 3,272 notifications, there were 528 (16%) in 2020 and 2,744 (84%) in 2021. Conclusion: It is necessary to combine the knowledge of professionals with the knowledge transmitted to users to advance in adherence of this contraception mechanism, because the lack of knowledge ends up being one of the main factors that lead to the withdrawal of the method.